Global Cardiac Surgery-Accessibility to Cardiac Surgery in Developing Countries: Objectives, Challenges, and Solutions - Salvatore Agati; Ermanno Bellanti (MDPI AG, 2023)
Cardiac surgery is a modern science in the history of medicine. The impact of cardiac disease, in terms of treatment and prognosis, has made this discipline indispensable to global health. In recent decades, the greatest investment has been dispensed to technological and material improvements to increase life expectancy. This surgery must address different epidemiological aspects dictated by the geography and economic-social conditions of the global populations. For this reason, it is progressively important to address the cardiac surgery accessibility disparity. Many scientific papers and international meetings have studied how cardiac surgery can be more accessible in various countries around the world. In this review, we analyze all the challenges, solutions, and suggestions that can make this surgery accessible to the entire global population, with the purpose of reducing its disparity across all seven continents. For a long time, high-income countries have invested in technological capabilities and experimental advancements without caring about unequal access in the rest of the world. We believe that it is time to reverse this growth trajectory, placing the accessibility and distribution of surgical science as a priority, which is significant for the right to health of all people worldwide. This is the real new challenge in cardiosurgery.